Transnationals and Governments / Recent Policies in Japan, France, Germany, the United States and Britain - Bailey David; Harte George; Sugden Roger (Rouledge, 1994)
The authors outline the various policies that the world's major economies have adopted to cope with the unique issues created by transnationals. Acknowledgements, Introduction: A Spectrum of Policy Approaches, Japan, France, Germany, United States, Britain, Issues of Concern, Index.